Rearticulating New York Times v. Sullivan as a Social Duty to Journalists. (2nd January 2017) - Edmondson, Aimee
Abstract : During the frenzied run of presidential primaries in 2016, Republican nominee Donald Trump vowed to "open up" libel laws to make suing the media easier. This apparent attempt to resurrect seditious libel brought a flurry of debate about how American libel laws might be altered in this context. "We are going to have people sue you like you've never got sued before, " Trump said. This article seeks to rearticulate the landmark New York Times v. Sullivan decision as a case about social duty and the duty that is owed to journalists in an increasingly contentious political climate. I argue that protecting this right to criticize public officials and public figures is as important as ever in our democratic system. Sullivan was a case about civil rights, about the right of African-American leaders and the media to cover and criticize how the police behaved in the 1960s when faced with the social revolution of the civil rights movement. This essay also focuses on three previously unstudied cases filed by police officers in the New York area in the 1960s. Sullivan secured our right to speak without a vindictive government bearing down on us via our legal system, but other cases decided outside the national spotlight suggest how that right was further cemented by the interaction of the media and the civil rights movement. Be it the brutality of police 50 years ago and today, or coverage of presidential candidates, I argue that journalists and the public are owed this right.